PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERNUANSA KARAKTER DAN KONTEKSTUAL PADA MATERI SISTEM REPRODUKSI UNTUK SISWA SMP - Falta, Lira Andika; Lufri, Lufri; Anhar, Azwir (Kolaboratif, 2013)
Biology learning is required the students’ understanding. In fact, the students tend to be more emphasize on memorizing rather than understanding, so that students cannot take benefits and meaning of the concept of biology learning. As a result, the quality of education become declined and  indirectly it decreases the value of the students’ character. One of efforts to resolve the problem is nuances character and contextual teaching aids. This study  aims to develop biology learning equipment nuances character and contextual in the material of  system reproduction  for Junior High School students in the form of lesson plans, teaching materials, students’ worksheets, and evaluation equipment that are valid, practical, and effective. The method of the research is the development research. Based on the result of the research, it was found that the learning media of biology  nuances character and contextual in material the system of reproduction for  Junior High School students that consist of lesson plan, teaching material, students’ worksheet and evaluation equipment  in the valid, practical, and effective category.